Negotiating Difference - Rosen, Lawrence (Maine Policy Review, 2004)
Lawrence Rosen’s commentary focuses on the legal aspect of Native American sovereignty throughout U.S. history, focusing on ramifications of the recent rise of casino gambling on Indian lands.
Keywords: Maine Indians; Native American sovereignty; gaming